Heritage Value and Stakeholders’ Perception of Four Geomorphological Landscapes in Southern Iceland - Bussard, Jonathan; Reynard, Emmanuel (Geoheritage, 2022)
Abstract This paper has two main objectives: (1) to assess the heritage value of four geomorphological landscapes in Southern Iceland from a geomorphological perspective and (2) to see to what extent the heritage values assigned by different local stakeholders overlap with this assessment. The concept of “geomorphological landscape”, that we define as a landscape whose geomorphological component is of heritage interest, is a scale of analysis that can be understood by different groups of people and that reflects subjective perceptions of the landscape. The evaluation of the heritage value of four geomorphological landscapes has shown that their geoscientific, aesthetic and cultural values are particularly high. Indeed, thanks to their rarity, representativeness, integrity and paleogeographic interest, all four sites have a geoscientific value ranging from 0.81 to 0.94 (the maximum possible score is 1). They also constitute spectacular and beautiful landscapes and have acquired a relevant cultural value because of the major impacts that volcanic eruptions and glaciers advances have had on the local population. Not surprisingly, the heritage awareness of managers of protected areas is high. The interviews also show that other types of stakeholders, such as tourism services providers, tourism promoters and representatives of local authorities, are also aware, to some extent, of the high geoscientific value. The societal and institutional recognition of the heritage value of these geomorphological landscapes is closely linked to their use as territorial resources for tourism.